The impact of reconstruction techniques on observer performance for the detection and characterization of small pulmonary nodules in chest CT of children under 13 years. Issue 100 (March 2018) - Verhagen, Martijn V.; Smets, Anne M.J.B.; van Schuppen, Joost; Deurloo, Eline E.; Schaefer-Prokop, Cornelia
Highlights: Maximum intensity projections improve detection of pulmonary nodules in children. Double reading is a powerful tool in chest CTs of children with a malignancy. Pulmonary nodule characterization benefits from 1 mm scans in three planes. Intrapulmonary lymph nodes occur in children with and without malignancy. Pulmonary nodules in children with cancer do not necessarily represent metastases. Abstract: Objective: To compare three different reconstruction techniques of CT data for the detection of pulmonary nodules in children under 13 years. Secondly to assess the prevalence of perifissural nodular opacities. Materials and methods: The study consisted of chest CTs of 31 children (median age 6.9 years, range 2.1–12.7), of whom 17 had known extra-thoracic malignancies. Four observers assessed three techniques for the presence of nodules: axial 5 mm maximum intensity projections (MIPs) used in conjunction with 1 mm slices (mode A), 1 mm slices alone (mode B) and 3 mm slices (mode C). All modes were available in 3D. Per mode sensitivities were determined above a certain threshold of reader agreement. Confidence level and reader agreement for identification of an opacity as nodule served as surrogate for quality of nodule characterization. Results: 103 nodules (median size 2.0 mm) were detected. Mode A yielded the highest interreader agreement (κ 0.336) and a superior sensitivity (71%, p = 0.003) compared to mode B and C (κ 0.218, sensitivity 57% and κ 0.247, sensitivity 56%, respectively). Mode B provided the highest confidence level and interreader agreement with respect to nodule identification (mean 4.3/5, κw 0.508). Double reading improved and evened interreader agreement for all modes (κ 0.450), mode A maintained the highest sensitivity (89.1%, p = 0.05–0.08). A median of 1 intrapulmonary lymph node/patient was seen in children with and without malignancy. Conclusion: MIP improves the detection of pulmonary nodules in chest CTs of children, but overall interreader agreement is only fair. Double reading represents a powerful tool to increase diagnostic reliability in chest CTs of children with a malignancy. Nodule characterization is best with 1 mm slices. Intrapulmonary lymph nodes occur in children with and without malignancy.